A Sulfite Biosensor Fabricated by Immobilization of Sulfite Oxidase on Aluminum Electrode Modified with Electropolymerized Conducting Film (Polyaniline) - Bahmani, B.; Moztarzadeh, F.; Hossini, M.; Rabiee, M.; Tahriri, M.; Rezvannia, M.; Alizadeh, M. (Asian Journal of Chemistry, 2010)
The development of a sulfite biosensor based on the immobilization of sulfite oxidase in electropolymerized conducting film (polyaniline) is described. The method for the determination of sulfite is based on the use of aluminum electrode modified with films of polyaniline. Electropolymerization of polyaniline and simultaneous immobilization of sulfite oxidase on the aluminum were performed in an aqueous solution containing sulfite oxidase. The sulfite biosensor constructed by cycling the potential scan between +1.2 and -0.5 V vs. saturated calomel electrode (SCE) that showed a sensitive response to sulfite with a linear calibration graph in the concentration ranges of 0.006-5 mM sulfite and detection limit 0.002 mM sulfite (S/N = 3). The stability study of the resulted sulfite biosensor revealed that formation of a passive film on the aluminum surface causes improved stability of the electroactive films formed on the electrode surface. The bioelectrochemical response of the enzymemodified electrode as a sulfite biosensor was investigated at different experimental conditions. The pH optimum of 8.5 was found when using phosphate buffer and the appropriate working temperature was accepted as 35 °C. The apparent Michaelis-Menten constant and the activation energy of the enzyme catalyzed reaction were also calculated.